2009
DOI: 10.1002/ejsp.665
|View full text |Cite
|
Sign up to set email alerts
|

The scaffolded mind: Higher mental processes are grounded in early experience of the physical world

Abstract: It has long been a staple of psychological theory that early life experiences significantly shape the adult's understanding of and reactions to the social world. Here we consider how early concept development along with evolved motives operating early in life can come to exert a passive, unconscious influence on the human adult's higher-order goal pursuits, judgments, and actions. In particular, we focus on concepts and goal structures specialized for interacting with the physical environment (e.g., distance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
288
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(313 citation statements)
references
References 77 publications
15
288
0
2
Order By: Relevance
“…These concepts do not require mental capacities of memory retrieval and comparison that do not develop until years later (Clark, 1973;Mandler, 1992). When these abstract concepts are later developed they tend to be "built upon" (and thus strongly associated with) these physical concepts to the extent they are analogous (i.e., share key features; Asch, 1946;Kelley, 1950;Lakoff & Johnson, 1980;Williams & Bargh, 2008a;Williams, Huang, & Bargh, 2009) and hence could activate one another or be used strategically for psychological intervention.…”
Section: What Mechanism Underlies Priming-based Interventions?mentioning
confidence: 99%
“…These concepts do not require mental capacities of memory retrieval and comparison that do not develop until years later (Clark, 1973;Mandler, 1992). When these abstract concepts are later developed they tend to be "built upon" (and thus strongly associated with) these physical concepts to the extent they are analogous (i.e., share key features; Asch, 1946;Kelley, 1950;Lakoff & Johnson, 1980;Williams & Bargh, 2008a;Williams, Huang, & Bargh, 2009) and hence could activate one another or be used strategically for psychological intervention.…”
Section: What Mechanism Underlies Priming-based Interventions?mentioning
confidence: 99%
“…A rationale for this idea is that many of our most important feelings and concepts -such as peace, love, or anger -lack a clear perceptual referent, which creates epistemic problems (Searle, 1998). People resolve such difficulties by scaffolding (Williams, Huang, & Bargh, 2009) abstract feelings and thoughts on perceptual dimensions -such as up-down, warm-cold, close-far, and dirty-clean -that are more concrete, immediate, and visceral, which in turn facilitates their intuitive understanding (Landau, Meier, & Keefer, 2010). Lakoff and Johnson (1999) further suggested that metaphor representation processes guide our thoughts like "a hidden hand".…”
Section: Personality Psychologymentioning
confidence: 99%
“…Finally, in a test of the association between physical and conceptual weight, participants who held a heavy clipboard rated various issues as more important relative to those who made their ratings while holding a light clipboard (Ackerman et al, 2010;Jostmann, Lakens, & Schubert, 2009). The reasons underlying these various effects may diverge -a functionalist account for biases in visual perception guiding action (Gibson, 1979); metaphoric priming as a developmental artifact of using sensorimotor information to learn higher-order reasoning (Williams, Huang, & Bargh, 2009) -but the relevance of physical experience remains consistent.…”
mentioning
confidence: 99%